Models of engineering in restaurant business - Hubar, Tetiana; Kuzmin, Oleg (My University, 2022)
The work presents an analytical review of engineering models for the distribution of responsibility between participants in construction projects depending on the type of contract. У роботі представлено аналітичний огляд моделей інжинірингу щодо розподілу відповідальності між учасниками будівельних проектів залежно від типу контракту.
Keywords: кафедра технології ресторанної і аюрведичної продукції; models of responsibility; engineering; EPC contract; EPCM contract; EPCS contract; PMC contract; моделі відповідальності; інжиніринг; контракт EPC; контракт EPCM; контракт EPCS; контракт PMC